Feasibility Study Of Bapak Gunoto's Know Business In Lebong District - Redi Redi; Tito Irwanto; Yudi Irawan Abi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the feasibility study of Mr. Gunoto's Tofu Business in Lebong Regency. The analytical method used is a feasibility study analysis from the financial aspect which includes Net Present Value (NPV), Internal Rate of Return (IRR), and Gross Benefit Cost Ratio (Gross B/C).The results of the Net Present Value (NPV) research show a positive number of Rp. 339,819,380,-, meaning that the expansion of Mr. Gunoto's Tofu Business in Lebong Regency can be said to be feasible for development. IRR (Internal Rate of Return) is known to be 30% greater than the percentage cost of capital (loan interest), namely 12% or 16%, meaning that business expansion is feasible for development. This shows that if funds for investment are saved or deposited in a bank with an interest rate of 12% and an interest rate of 16%, then the capital will grow faster if it is made into tofu business capital because it will grow at an interest rate equivalent to 30. Gross B/C greater than 1 (1.69 > 1) means that the development of Mr. Gunoto's tofu business in Lebong Regency is feasible for development.